1990
DOI: 10.1007/bf00002714
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy of the rhizosphere in forest soils of the eastern United States

Abstract: Chemical and mineralogical studies of forest soils from six sites in the northeastern and southeastern United States indicate that soil in the immediate vicinity of roots and fine root masses may show marked differences in physical characteristics, mineralogy and weathering compared to the bulk of the forest soil. Examination of rhizosphere and rhizoplane soils revealed that mineral grains within these zones are affected mechanically, chemically and mineralogically by the invading root bodies. In SEM/EDS analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(34 citation statements)
references
References 26 publications
2
31
0
Order By: Relevance
“…2), may indicate higher rates of mineral weathering in ECS compared to N-ECM soils. These findings are consistent with those of Arocena et al (1999) where amounts of mica and chlorite in ECS samples were significantly lower compared to N-ECM soils for subalpine fir, and they corroborate results from other studies (April and Keller 1990;Hinsinger et al 1991;Kodama et al 1994;Courchesne and Gobran 1997). In these four studies cited, bulk and rhizosphere materials were compared and soil minerals other than mica and chlorite (e.g., amphibole) were affected by increased weathering.…”
Section: Mineral Composition Of Ecs and N-ecm Soilssupporting
confidence: 90%
See 1 more Smart Citation
“…2), may indicate higher rates of mineral weathering in ECS compared to N-ECM soils. These findings are consistent with those of Arocena et al (1999) where amounts of mica and chlorite in ECS samples were significantly lower compared to N-ECM soils for subalpine fir, and they corroborate results from other studies (April and Keller 1990;Hinsinger et al 1991;Kodama et al 1994;Courchesne and Gobran 1997). In these four studies cited, bulk and rhizosphere materials were compared and soil minerals other than mica and chlorite (e.g., amphibole) were affected by increased weathering.…”
Section: Mineral Composition Of Ecs and N-ecm Soilssupporting
confidence: 90%
“…In the rhizosphere zones, both physical and chemical processes increase rates of mineral weathering. The pressures exerted by growing roots and associated fungal hyphae could mechanically alter minerals by causing realignment, bending, and fracturing (April and Keller 1990). In addition, Robert and Berthelin (1986) showed micrographs of hyphae probing between mica flakes to extract essential K + .…”
Section: Mineral Composition Of Ecs and N-ecm Soilsmentioning
confidence: 99%
“…The extensive transformation of biotite to vermiculite has been attributed to root-induced pH decreases in the rhizosphere and acid dissolution of the mica structure (104). In a similar experimental study (93), plant roots and ectomycorrhizal fungi actively produced oxalate and increased biotite weathering when they were stressed for K and Mg. Plant roots and associated microbial populations also physically disrupt sheet silicates, exposing new surface area for chemical alteration (107).…”
Section: Application Of Insights From the Lichen-mineral Interface Tomentioning
confidence: 99%
“…Concerning the Al compounds, April and Keller [29] found that chemical interactions between roots and rhizosphere minerals included the precipitation of amorphous Al oxides and hydroxides within the cells of mature roots. Cloutier-Hurteau et al [30] revealed that Al-organic complexes were generally the dominant species in the rhizosphere of forest soils.…”
Section: Oxide-encrusted Root Cellsmentioning
confidence: 99%